Chronological changes of viral shedding in adult inpatients with Omicron infection in Shanghai, China - Zhou, Xinru; Huang, Xiaochun; Sun, Tingting; Jin, Xiaolan; Tian, Zhaofeng; Xue, Miao; Kang, Jinsong; Gao, Bai; Xu, Aijing; Chen, Yi; Jia, Yin; Liu, Shanrong (Frontiers in Immunology, 2023)
Background Coronavirus disease 2019 (COVID-19) caused by the Omicron variant occurred in Shanghai, China, but its clinical characteristics and virology have not been comprehensively described. Methods This retrospective cohort study included adult inpatients (≥18 years) diagnosed with COVID-19 at Changhai Hospital. Laboratory and clinical data were obtained from electronic medical records to investigate the clinical characteristics of COVID-19 and the variations in the patients’ laboratory indexes were examined. Results The symptoms of COVID-19 caused by the Omicron variant were relatively mild. Upper respiratory tract specimens yielded higher positive detection rates than lower respiratory tract and intestinal specimens. Peak COVID-19 viral load was reached at the time of admission; quantification cycle (Cq) values increased to approximately 35 after 8.54 days. In vivo viral shedding duration correlated with age and disease severity (p<0.05). The older the patient and the more severe the disease, the longer the duration of viral shedding was. Portion parameters of blood routine, coagulative function, clinical chemistry, and inflammatory factor showed a certain correlation with the SARS-CoV-2 viral load. Conclusions Virus replication and shedding are rapid in Omicron-positive patients; COVID-19 in these patients is characterized by acute onset, mild symptoms, and fast recovery. Older patients and those with more severe disease demonstrate prolonged virus shedding. Routine hematological indexes can reveal disease severity and help clinically evaluate the patient’s condition.